FtNAC31, a Tartary buckwheat NAC transcription factor, enhances salt and drought tolerance in transgenic Arabidopsis - Zhao, Jia-Li (Plant physiology and biochemistry : PPB, 2022)
Copyright © 2022 Elsevier Masson SAS. All rights reserved.